Assessing Empathy across Childhood and Adolescence: Validation of the Empathy Questionnaire for Children and Adolescents (EmQue-CA) - Overgaauw, Sandy; Rieffe, Carolien; Broekhof, Evelien; Crone, Eveline A.; Güroğlu, Berna (Frontiers in Psychology, 2017)
Empathy plays a crucial role in healthy social functioning and in maintaining positive social relationships. In this study, 1250 children and adolescents (10-15 year olds) completed the newly developed Empathy Questionnaire for Children and Adolescents (EmQue-CA) that was tested on reliability, construct validity, convergent validity, and concurrent validity. The EmQue-CA aims to assess empathy using the following scales: affective empathy, cognitive empathy, and intention to comfort. A Principal Components Analysis, which was directly tested with a Confirmatory Factor Analysis, confirmed the proposed three-factor model resulting in 14 final items. Reliability analyses demonstrated high internal consistency of the scales. Furthermore, the scales showed high convergent validity, as they were positively correlated with related scales of the Interpersonal Reactivity Index (Davis, 1983). With regard to concurrent validity, higher empathy was related to more attention to others’ emotions, higher friendship quality, less focus on own affective state, and lower levels of bullying behavior. Taken together, we show that the EmQue-CA is a reliable and valid instrument to measure empathy in typically developing children and adolescents aged ten and older.